Health as Human Capital in Entrepreneurship: Individual, Extension, and Substitution Effects on Entrepreneurial Success. (January 2021) - Hatak, Isabella; Zhou, Haibo
This study investigates how entrepreneurial health and spousal health influence monetary and non-monetary entrepreneurial success. Drawing on human capital theory in combination with a family embeddedness perspective on entrepreneurship and applying actor–partner interdependence models to longitudinal data, we conclude that overall spousal health constitutes an important extension of entrepreneurs' human capital influencing entrepreneurial success. This study further contributes to human capital research by offering interesting insights and novel theorizing on substitution effects for different types of entrepreneurial human capital, and adds to a biological perspective on entrepreneurship by considering the differential role of biological sex in the health–success relationship.